2009
DOI: 10.1002/adem.200900104
|View full text |Cite
|
Sign up to set email alerts
|

Influence of TiO2 Nanoparticles Incorporated into Elastomeric Polyesters on their Biocompatibility In Vitro and In Vivo

Abstract: Polymer-matrix nanocomposites are an emerging group of biomaterials with enhanced mechanical characteristics and biological performance. Nanocomposites containing ceramic nanofillers embedded in a thermoplast or thermoset polymer matrix are an interesting group of materials in which desirable stiffness and biocompatibility can be achieved. However, many of these systems are rather stiff materials of limited elongation and, thus, application. Therefore, thermoplastic elastomers (TPE), as materials of high flexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…In 2009, Miroslawa et al 41 studied the in vitro and in vivo cytotoxicity of silicone elastomer with TiO 2 nanoparticles. They revealed that silicone elastomer containing TiO 2 nanoparticles was non-toxic by a simple propidium iodide (PI) exclusion test using mouse fibroblast 3T3 cell line.…”
Section: Mtt Assaymentioning
confidence: 99%
“…In 2009, Miroslawa et al 41 studied the in vitro and in vivo cytotoxicity of silicone elastomer with TiO 2 nanoparticles. They revealed that silicone elastomer containing TiO 2 nanoparticles was non-toxic by a simple propidium iodide (PI) exclusion test using mouse fibroblast 3T3 cell line.…”
Section: Mtt Assaymentioning
confidence: 99%
“…So, many efforts have been made to overcome this problem and to enhance the filler-matrix compatibility through surface modification of the used nanoparticles [10][11][12][13]. So far, surface modified nano-TiO 2 particles have been widely used in the field of polymer-based nanocomposites [14][15][16][17][18][19][20]. The most research activities have been focused on the surface modification of nano-TiO 2 using silane coupling agents such as 3-aminopropyltriethoxysilane (APTS) [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…El‐Fray et al evaluated the in vivo and in vitro cytotoxicity of silicone elastomers with added TiO 2 nanoparticles. They reported that these elastomers were nontoxic, based on a simple promidium iodide exclusion assessment method using a mouse fibroblast 3T3 cell line.…”
Section: Discussionmentioning
confidence: 99%